Efektivitas Pelatihan Penanganan Tersedak pada Anak Terhadap Pengetahuan, Sikap, dan Keterampilan Ibu - Maghfiroh, Isni Lailatul; Suratmi, Suratmi; Samantha Aisyah, Harnina (Pustaka Galeri Mandiri, 2025)
Choking is a common emergency in children and infants. Failure to respond quickly can lead to death. Mothers play a crucial role as first responders, yet many mothers are underprepared. Choking management training programs are crucial to help mothers respond quickly and appropriately at home. The purpose of this study was to determine the effect of choking management training on mothers' knowledge, attitudes, and skills. This study used a quasi-experimental design with a single-group pre and post-test. A total of 49 mothers participated in the study. The training program consisted of education about the risks of choking, recognizing the signs and symptoms, and demonstrating choking management techniques. Knowledge, attitudes, and skills were measured using questionnaires before and after the intervention and analyzed using a paired t-test. The results showed a significant increase in knowledge and skills with a p-value of 0.000 (p<0.05). However, no significant difference in attitudes before and after the training (p-value: 0.214 (p>0.05)). Training programs that include education and demonstrations effectively increase knowledge and skills regarding choking response, but are insufficient to rapidly change attitudes. Improved knowledge and skills are driven by demonstrations that provide direct sensory experience and facilitate the absorption of technical information. On the other hand, the lack of significant change in attitudes may be due to the influence of psychological factors and internal beliefs. Changes in these factors require more time and repeated experience. Furthermore, ongoing support is crucial to strengthen mothers' psychological preparedness and attitudes in emergencies.